Laying the Groundwork for Health: Eating Behaviour and Physical Activity in Preschoolers in Split-Dalmatia County, Croatia - Dora Bučan Nenadić; Lucija Štrkalj; Klara Zloić; Antonela Matana; Marija Selak; Matea Smoljo; Antonia Vlašić; Vanessa Ivana Peričić; Ela Kolak Gaurina (Children)
Background/Objectives: Overweight children and childhood obesity are growing public health concerns influenced by early-life nutrition and lifestyle. Irregular eating patterns, sedentary behaviour, and maladaptive eating behaviours significantly contribute to excess weight gain in children. This cross-sectional study comprehensively assessed physical activity, sleep, anthropometric parameters, and eating behaviours in preschool children in Split, Croatia, examining associations between eating behaviours and nutritional status indicators. Methods: A total of 429 children aged 4 to 7 years were recruited from kindergartens in Split-Dalmatia County. Parents completed a lifestyle questionnaire and the Children’s Eating Behaviour Questionnaire (CEBQ). Anthropometric measurements (weight, height, middle upper arm circumference, waist circumference) were recorded and BMI-for-age z-scores calculated. Physical activity and sleep patterns were assessed based on parental reports. Results: A total of 66% of the children had a healthy body weight, 12.6% were underweight, and 21.4% were overweight or obese. Significant sex differences were found in the CEBQ subscale “Slowness in Eating” (p = 0.04). Overweight or obese children showed a higher food responsiveness, while underweight/normal-weight children had greater emotional undereating and slowness in eating. No significant sex differences were observed regarding physical activity. Girls exhibited significantly more frequent daytime napping than boys. Conclusions: This study shows a significant prevalence of overweight and obese preschool children in Split, Croatia. The results underline the importance of promoting healthy eating behaviours and physical activity from an early age. This is the first study applying CEBQ in the Croatian population and suggests that the interventions should target diet quality and unfavourable eating behaviours to prevent future health risks.